What Is the Optimal Antibiotic (Type, Dose and Route of Administration) Treatment for Infections After Foot/Ankle Fracture or Fusion Procedures?. (July 2019) - Pedowitz, David; Stull, Justin
Recommendation: The optimal antibiotic treatment after foot/ankle fractures or fusion should be determined based on the result of culture. In the absence of culture results, administered antibiotics should include coverage against common pathogens such as Staphylococcus aureus . Level of Evidence: Strong. Delegate Vote: Agree: 100%, Disagree: 0%, Abstain: 0% (Unanimous, Strongest Consensus).